2020
DOI: 10.1136/bmjdrc-2020-001457
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbohydrate quality and amount on plasma lactate: results from the OmniCarb trial

Abstract: IntroductionPlasma lactate is a marker of non-oxidative glucose metabolism associated with progression to diabetes. We examined the effect of carbohydrate quality (glycemic index (GI)) and amount (%kcal) on plasma lactate. We hypothesized that low GI (≤45 (g)) versus high (≥65 (G)) and low %kcal from carbohydrate (40% kcal (c)) versus high (58% kcal (C)) each would reduce lactate levels.Research design and methodsWe measured lactate in OmniCarb, a randomized, cross-over trial of four diets in overweight/obese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
1
2
Order By: Relevance
“…Based on this, it is also of particular interest to investigate the blood lactate kinetics measured during the CPX testing. Blood lactate values were not significantly different in our study in comparison to both diets at baseline—yet after 10 min of testing the blood lactate response of the LC group showed an altered kinetic, which is in line with previous findings from Hu et al [ 26 ]. In their study, it was shown that LC diets reduce resting plasma lactate levels; however, if this finding impacts functional capacity and physiological markers need to be investigated during a longer period of carbohydrate-restricted feeding, larger cohorts and during varying types of exercise accompanied by different intensities.…”
Section: Discussionsupporting
confidence: 92%
“…Based on this, it is also of particular interest to investigate the blood lactate kinetics measured during the CPX testing. Blood lactate values were not significantly different in our study in comparison to both diets at baseline—yet after 10 min of testing the blood lactate response of the LC group showed an altered kinetic, which is in line with previous findings from Hu et al [ 26 ]. In their study, it was shown that LC diets reduce resting plasma lactate levels; however, if this finding impacts functional capacity and physiological markers need to be investigated during a longer period of carbohydrate-restricted feeding, larger cohorts and during varying types of exercise accompanied by different intensities.…”
Section: Discussionsupporting
confidence: 92%
“…In obese subjects, high levels of fasting plasma lactate are used as a marker of non-oxidative glucose metabolism and is associated with impaired glucose handling. 66 In contrast, we observed that CON had increased lactate during OGTT after PE but that glucose tolerance was not affected, whereas END showed a decrease in lactate but had reduced glucose tolerance. We do not know if the alterations in circulating lactate reflected a change in metabolism or an increase in gluconeogenesis.…”
Section: Discussioncontrasting
confidence: 71%
“…The suppressed lactate response during a glucose load can therefore assist in preserving fat oxidation to spare glucose for glycogen resynthesis, providing that the observed differences in lactate are sufficient to alter lipolysis. In obese subjects, high levels of fasting plasma lactate are used as a marker of non‐oxidative glucose metabolism and is associated with impaired glucose handling 66 . In contrast, we observed that CON had increased lactate during OGTT after PE but that glucose tolerance was not affected, whereas END showed a decrease in lactate but had reduced glucose tolerance.…”
Section: Discussioncontrasting
confidence: 67%
“…Indeed, chronic and acute hyperglycemia can trigger platelet activation [ 26 , 27 ], while in diabetic patients, the production of several growth factors involved in initiating and sustaining the healing process is compromised [ 25 ]; for example, vascular endothelial growth factor (VEGF) and transforming growth factor-beta (TGF-beta) protein expression is reduced in diabetic dermal wounds [ 28 , 29 ]. Recently, plasma lactate has emerged as an early indicator of aberrant metabolism, specifically, development of insulin resistance and diabetes mellitus [ 30 ]. In the context of wound healing, lactate accumulates as a consequence of both aerobic and anaerobic glycolysis following microcirculation disruption, immune activation, and increased cell proliferation [ 31 ].…”
Section: Introductionmentioning
confidence: 99%